Development of a Mobile Application for Teaching Transmission Line Theory - Salmi, Khalid; Magrez, Hamid; Sefraoui, Hanane; Ziyyat, Abdelhak (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The teaching of transmission line theory in electrical engineering courses must be tailored to an audience which is increasingly reluctant to adhere to abstract disciplines. In our opinion, the best solution to make transmission line courses more attractive is to offer practical applications and intensively use of mathematical computer-aided teaching tools to overcome, at the beginning, the difficulties linked to the theory. Indeed, transmission line theory comes alive when the travelling waves are animated on a screen (smartphone, tablets, laptop, etc.). Fundamental concepts such as “progressive wave”, “reflected wave” and “load matching” could be easily demonstrated in the classroom or at home. Transmission line simulations are applied to problems using connections to shunt, open, matched and unmatched loads, and show how the signal waveforms arise from one end to another. The proposed Android-based animations are used with a sinusoidal generator to illustrate the evolution to the sinusoidal steady state and allow learners to easily handle the corresponding Smith chart. Students are encouraged to run those applications at home as a computational laboratory to verify their solutions to homework problems. This article introduces simple Android-based virtual tools for the investigation and visualization in real time of waves traveling along a terminated finite-length transmission line, without and with faults between the source and the load. The package can be used as an educational tool in various lectures or homework to aid teaching high frequency electronics and transmission lines theory.